Determinants of premature familial arterial thrombosis in patients with juvenile ischaemic stroke - Pezzini, Alessandro; Grassi, Mario; Lodigiani, Corrado; Patella, Rosalba; Gandolfo, Carlo; Zini, Andrea; DeLodovici, Maria Luisa; Paciaroni, Maurizio; Del Sette, Massimo; Toriello, Antonella; Musolino, Rossella; Calabrò, Rocco Salvatore; Bovil, Paolo; Adami, Alessandro; Silvestrelli, Giorgio; Sessa, Maria; Cavallini, Anna; Marcheselli, Simona; Bonifati, Domenico Marco; Checcarelli, Nicoletta; Tancredi, Lucia; Chiti, Alberto; Del Zotto, Elisabetta; Spalloni, Alessandra; Costa, Paolo; Giacalone, Giacomo; Ferrazzi, Paola; Poli, Loris; Andrea, Morotti; Maurizia, Rasura; Simone, Anna Maria; Gamba, Massimo; Cerrato, Paolo; Micieli, Giuseppe; Melis, Maurizio; Massucco, Davide; De Giuli, Valeria; Pepe, Daniele; Iacoviello, Licia; Padovani, Alessandro (Thrombosis and Haemostasis, 2015)
Factors predicting family history (FH) of premature arterial thrombosis in young patients with ischaemic stroke (IS) have not been extensively investigated, and whether they might influence the risk of post-stroke recurrence is still unknown. In the present study we analysed 1,881 consecutive first-ever IS patients aged 18–45 years recruited from January 2000 to January 2012 as part of the Italian Project on Stroke in Young Adults (IPSYS). FH of premature arterial thrombosis was any thrombotic event [IS, myocardial infarction or other arterial events event] > 45 years in proband’s first-degree relatives. Compared with patients without FH of premature arterial thrombosis, those with FH (n= 85) were more often smokers (odds ratio [OR], 1.94; 95 % confidence interval [CI], 1.21–3.09) and carriers of procoagulant abnormalities (OR, 3.66; 95 % CI, 2.21–6.06). Smoking (OR, 2.48; 95 % CI, 1.20–5.15), the A1691 mutation in factor V gene (OR, 3.64; 95 % CI, 1.31–10.10), and the A20210 mutation in the prothrombin gene (OR, 8.40; 95 % CI 3.35–21.05) were associated with FH of premature stroke (n = 33), while circulating anti-phospholipids to FH of premature myocardial infarction (n = 45; OR, 3.48; 95 % CI, 1.61–7.51). Mean follow-up time was 46.6 ± 38.6 months. Recurrent events occurred more frequently in the subgroup of patients with FH of premature stroke [19.4 %); p = 0.051] compared to patients without such a FH. In conclusion, young IS patients with FH of premature arterial thrombosis exhibit a distinct risk-factor profile, an underlying procoagulant state and have worse vascular prognosis than those with no FH of juvenile thrombotic events.
Keywords: Stroke in young adults; cohort studies; risk factors in epidemiology